Risk factors associated with mortality in patients with SARS-CoV-2 pneumonia in a Level I Social Security Hospital, Peru-La Libertad - Arana-Calderón, César Alejandro (2022)
Objective: To identify demographic, clinical, laboratory and treatment characteristics associated with mortality in hospitalized patients with SARS-CoV-2 pneumonia in a Level I Hospital of Peruvian Social Security, at La Libertad Network. Materials and Method: Retrospective cohort study. Cox proportional hazards model was used, calculating crude and adjusted hazard ratios (HR), and the Kaplan-Meier estimator was used to evaluate the overall survival curve and for each factor. Results: Of the 158 patients, the diagnosis was confirmed in 79.11%. Nearly 70% (68.99%) were men, the global median age was 65 years (IQR: 52-77), and it was higher in deceased subjects 69 years old (IQR: 61-80 years). Little more than half of this population (53.80%) had comorbidities, such as high blood pressure (27.85%), obesity (22.78%), and diabetes mellitus (13.92%). The median duration of symptoms prior to admission was 9 days (IQR: 6-11 days). HRs were determined for oxygen saturation less than 80% on admission with 0.21 FIO2, leukocytosis with associated lymphopenia, oxygen requirement at 0.80 FIO2 on admission, and moderate-severe ARDS. Such values were 1.54, 1.98, 2.07 and 2.91, respectively. Conclusions: The development of moderate-severe ARDS on admission, leukocytosis associated with lymphopenia, less than 80% hypoxemia on admission at 0.21 FIO2, and high-flow oxygen requirement since admission with 0.80 FIO2, were the only risk factors for mortality.